1973
DOI: 10.1172/jci107450
|View full text |Cite
|
Sign up to set email alerts
|

Early Estimation of Myocardial Damage in Conscious Dogs and Patients with Evolving Acute Myocardial Infarction

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(41 citation statements)
references
References 17 publications
0
38
1
2
Order By: Relevance
“…After coronary artery occlusion, the speed at which acutely ischemic cells become irreversibly injured is not uniform and depends on their location as well as on a number of other factors (3)(4)(5). However, the fate of these cells can be modified, at least in the short term, by various therapeutic interventions, as was shown indirectly by epicardial ST segment (4,5) and QRS (6) mapping, by the relationship between epicardial ST segment elevation and the creatine kinase (CK)1 content ofthe sibjacent myocarditum (4,5), and by serial changes in serum CK activity (7,8). These experiments involved the uise of the indirect techniques mentioned above and the examination of the effects of interventions 24 h after the occluision, when the process of infaretion is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…After coronary artery occlusion, the speed at which acutely ischemic cells become irreversibly injured is not uniform and depends on their location as well as on a number of other factors (3)(4)(5). However, the fate of these cells can be modified, at least in the short term, by various therapeutic interventions, as was shown indirectly by epicardial ST segment (4,5) and QRS (6) mapping, by the relationship between epicardial ST segment elevation and the creatine kinase (CK)1 content ofthe sibjacent myocarditum (4,5), and by serial changes in serum CK activity (7,8). These experiments involved the uise of the indirect techniques mentioned above and the examination of the effects of interventions 24 h after the occluision, when the process of infaretion is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…For example, measurement of serum creatine phosphokinase and lactate dehydrogenase isoenzymes after suspected myocardial infarction both confirms the diagnosis and may be used to estimate the volume of infarcted muscle (15,16). In 1975, Lieberman (17) first reported that angiotensin-converting enzyme (ACE; EC 3.415.1, peptidyl dipeptidase)l is elevated in sera of patients with active pulmonary sarcoidosis.…”
mentioning
confidence: 99%
“…13 CK is released in skeleton muscles, hence the quantitative relation between serum CK depletion attack, which are responsible for many of the false positive enzymes elevation reported particularly in early studies, when iso-enzymes study were not available. [14][15][16] Several studies have shown the elevated relation between peak serum enzyme activities after myocardial infarction. [17][18][19] Lindsay et al 20 are argued that the metabolic effect that leads to increase in flux may fully and partially reversible, therefore the elevation of CK-MB could signify the adverse effect on the myocardial cell resulting from something other than necrosis or ischemia.…”
Section: Discussionmentioning
confidence: 99%